Implementasi Etika Bisnis Islam dalam Transaksi Jual Beli Pedagang Busana Muslim di Kawasan Religi Sunan Ampel Surabaya - Syaifullah, Muhammad Ilham (Lembaga Yasin AlSys, 2023)
Islamic business ethics is a way or morals used in carrying out business activities that cover all aspects based on the Qur'an and hadith as well as applicable norms. Islamic business ethics includes five principles including the principle of unity, the principle of justice, the principle of free will, the principle of responsibility and the principle of truth. In carrying out business activities, a Muslim is required to always apply the principles of Islamic business ethics in accordance with Islamic law. This study aims to find out how the process of buying and selling transactions and the application or implementation of Islamic business ethics in buying and selling transactions of Muslim fashion traders in the Religious Area of Sunan Ampel Surabaya. The method used in this research is using descriptive qualitative method. Sources of data in this study using primary and secondary data sources. Data collection techniques using the method of observation, interviews and documentation. Informants in this study include several parties including market managers, Muslim clothing traders and Muslim clothing buyers in the Sunan Ampel Religious Area, Surabaya. Based on the results of the interviews and observations, the researchers formulated the results of this study, namely 1) The process of buying and selling transactions for fashion merchants includes sellers and buyers, consent and acceptance, goods purchased and replacement exchange rates. 2) The application of Islamic business ethics has been well implemented by Muslim fashion traders. But there are still traders who show impolite and unfriendly attitudes towards buyers. This can be due to traders who do not fully understand Islamic business ethics.